Sony BMG Corporation : digital rights management - Curry, Joseph J., (SAGE Knowledge. Cases., 2017)
On October 31, 2005, computer programmer Mark Russinovich wrote in his online blog that listening to his new Sony BMG CD on his computer had turned into more of a trick than treat. Russinovich discovered that the anti-piracy software on his Sony CD had installed a hidden program that made his computer vulnerable to potential viruses. Within hours, Russinovichs article became a hot topic across the web. Hundreds of other sites linked to his blog and the security hole created by Sonys software became a headline in major U.S. and British newspapers. Sony BMG initially rejected the uproar against the software as technobabble, and the digital rights management issue quickly turned into a public relations and legal nightmare. Since CD copy protection is still an experiment in progress, Sony must balance its desire to protect its intellectual property with consumer rights concerns.